A Review of the Potential for Cardiometabolic Dysfunction in Youth with Spina Bifida and the Role for Physical Activity and Structured Exercise - Kevin R. Short; Dominic Frimberger (International Journal of Pediatrics)
Children and adolescents who have decreased mobility due to spina bifida may be at increased risk for the components of metabolic syndrome, including abdominal obesity, insulin resistance, and dyslipidemia due to low physical activity. Like their nondisabled peers, adolescents with spina bifida that develop metabolic risk factors early in life have set the stage for adult disease. Exercise interventions can improve metabolic dysfunction in nondisabled youth, but the types of exercise programs that are most effective and the mechanisms involved are not known. This is especially true in adolescents with spina bifida, who have impaired mobility and physical function and with whom there have been few well-controlled studies. This paper highlights the current lack of knowledge about the role of physical activity and the need to develop exercise strategies targeting the reduction of cardiometabolic risk and improving quality of life in youth with spina bifida.